Pharmacokinetic studies of 68Ga-labeled bombesin (68Ga-BZH3) and F-18 FDG PET in patients with recurrent gliomas and comparison to grading: preliminary results - Dimitrakopoulou-Strauss, Antonia; Seiz-Rosenhagen, Marcel; Tüttenberg, Jochen; Schmieder, Kirsten; Eisenhut, Michael; Haberkorn, Uwe; Strauss, Ludwig G. (Clinical nuclear medicine, 2011)
Purpose: - Dynamic PET studies with a 68Ga-Bombesin analog, the 68Ga-BZH3, were performed in patients with highly suspected recurrent gliomas to investigate the effect of the receptor scintigraphy on tumor grading. Furthermore, dynamic F-18 Fluorodeoxyglucose (FDG) studies were performed for comparison. - Methods: - The study consisted of 15 patients with histologically confirmed recurrent gliomas. Dynamic PET scans using 68Ga-BZH3 and FDG were obtained on 2 different days within 1 week. Multivariate analysis was used for the evaluation of the kinetic data. Standardized uptake values were calculated and a compartment (2-tissue) as well as a noncompartment model was used for data evaluation of both tracers. - Results: - The evaluation includes 6 patients with a WHO II, 6 patients with a WHO III, and 3 patients with a WHO IV recurrent gliomas. Of the 15 patients, 10 patients demonstrated an increased 68Ga-BZH3 uptake visually, 3 of them with a WHO II, 4 with a WHO III, and 3 with a WHO IV tumor. Of the 15 patients, 6 patients revealed an enhanced FDG metabolism visually, 3 of them with a WHO II, and 3 with a WHO III. None of the 3 patients with WHO IV tumor demonstrated an enhanced FDG-uptake. Discriminant analysis based on a combination of FDG influx and binding potential of 68Ga-BZH3 best discriminated between low- and high-grade gliomas with a correct classification rate of 100%. - Conclusions: - 68Ga-BZH3 seems to be helpful in patients with recurrent gliomas for the differentiation between low- and high-grade gliomas. Overall, the quantitative evaluation was superior to the visual analysis and the parameters of the 68Ga-BZH3 kinetics were more helpful than those of FDG for the differentiation between low- and high-grade gliomas.
Im Titel ist "68" bei "Ga" hochgestellt
Im Titel ist "3" bei "68Ga-BZH" tiefgestellt
Gesehen am 13.06.2022